2023
DOI: 10.3390/ma16134851
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Filtration Performance of Composite Air Filter Materials Synthesized Using Different Impregnated Porous Media

Abstract: Indoor environment quality is currently a hot research topic. In this study, composite air filter materials were synthesized using different impregnated porous medium materials, and their filtration performance and structural parameters were analyzed. The results showed that composite filter materials’ structures changed at the fibers’ surfaces when synthesized using different porous medium material layers. The filtration efficiency of composite filter materials synthesized using different porous media reached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…Through the microstructure, it could also be seen that the resistance could be reduced by changing the fibers’ own structure, without affecting the filtration efficiency. According to the relevant literature [ 19 ], fibers can be composed of porous media with a large specific surface area. When passing through dust sources, this can not only efficiently capture pollutants, but also provide multi-channel airflow, thereby reducing the resistance without affecting the filtration efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the microstructure, it could also be seen that the resistance could be reduced by changing the fibers’ own structure, without affecting the filtration efficiency. According to the relevant literature [ 19 ], fibers can be composed of porous media with a large specific surface area. When passing through dust sources, this can not only efficiently capture pollutants, but also provide multi-channel airflow, thereby reducing the resistance without affecting the filtration efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the preparation and optimization of fiber materials have always been among the main directions in research on high-performance filtration materials [ 17 ]. Domestic and foreign scholars have achieved certain results through extensive related research [ 18 , 19 , 20 , 21 ]. The focus of such research is on improving the efficiency of filter materials [ 18 ], as well as the development of new materials [ 19 , 20 , 21 ], and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the relatively long research cycle, complex preparation processes, high costs, high difficulty in operation, and unstable performance of new air filter materials [14,15], it is difficult to promote new air filter materials on a large scale in a short period of time. In particular, in response to the demand for more frequent use of filters in the post-pandemic era [16], the performance requirements for air filters will become higher compared to the past.…”
Section: Introductionmentioning
confidence: 99%
“…For most bacteria and viral microorganisms, the size is on the micron or submicron scale. For example, relevant studies have shown that viruses are about 100 nm in size [16]. These small particles in the air could be efficiently captured by the filter fibers, which are very small and dense.…”
Section: Introductionmentioning
confidence: 99%